Pengaruh Brand Image Terhadap Keputusan Pembelian Tiket Pesawat pada Maskapai Super Air Jet di Bandar Udara Internasional Yogyakarta - Meigy Ismi Abustan; Andityo Pujo Laksana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the past two years, Super Air Jet has successfully established a significant brand image through the implementation of a Low-Cost Carrier (LCC) strategy with affordable fares. This strategy is relevant to Indonesia's needs as a developing country requiring fast and affordable transportation. The fresh and trend-following approach has attracted consumer interest. The researcher seeks to further explore the influence of the LCC brand image on passengers' purchase decisions, considering the rapid technological developments that affect information exchange and potential risks to brand image. This study aims to determine whether there is an influence, and to what extent brand image affects the purchase decision of airplane tickets for Super Air Jet at Yogyakarta International Airport. This research uses a descriptive quantitative approach, and the types of data used are primary and secondary data. The data collection technique used in this research is through the distribution of questionnaires to passengers who have flown with Super Air Jet on the BPN-YIA or YIA-BPN routes at Yogyakarta International Airport. The study concludes that brand image has a positive and significant influence of 73.9% on passenger satisfaction, while 26.1% is influenced by other variables not examined in this study. This is evidenced by the result of Tcount > Ttable, i.e., 16.656 > 1.984.